2018
DOI: 10.1111/faf.12270
|View full text |Cite
|
Sign up to set email alerts
|

Colonizing Islands of water on dry land—on the passive dispersal of fish eggs by birds

Abstract: The vast majority of global freshwater ecosystems are small lakes with less than 100 m2 surface area. These lakes are often unconnected to other water bodies but frequently host fish populations. Existing explanations for how fish colonize such remote habitats often involve birds as vectors transporting fish eggs as propagules. In this study, we aim to quantify the prevalence of these explanations among relevant societal groups as well as their scientific knowledge basis. We analyzed entries in online blogs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 50 publications
0
24
0
1
Order By: Relevance
“…In comparison, in two out of seven unmanaged lakes, one individual of either non-native P. parva or non-native A. nebulosus, were detected, showing that also unmanaged lakes receive non-natives. Illegal stocking from anglers interested in establishing desired species in a certain waterbody or releases of fish by owners of garden ponds or other private people, as indicated by a golden variety of S. erythrophthalmus found in one unmanaged lake, have been reported vectors for fish dispersal around the globe (Copp et al, 2005a;Hirsch et al, 2018;Johnson et al, 2009). Indeed, illegal releases, often by non-angling stakeholders, rather than purposely planned fisheries management, constitutes the most important pathway for the transfer of non-natives fishes across the world .…”
Section: Presence Of Non-native Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, in two out of seven unmanaged lakes, one individual of either non-native P. parva or non-native A. nebulosus, were detected, showing that also unmanaged lakes receive non-natives. Illegal stocking from anglers interested in establishing desired species in a certain waterbody or releases of fish by owners of garden ponds or other private people, as indicated by a golden variety of S. erythrophthalmus found in one unmanaged lake, have been reported vectors for fish dispersal around the globe (Copp et al, 2005a;Hirsch et al, 2018;Johnson et al, 2009). Indeed, illegal releases, often by non-angling stakeholders, rather than purposely planned fisheries management, constitutes the most important pathway for the transfer of non-natives fishes across the world .…”
Section: Presence Of Non-native Fishmentioning
confidence: 99%
“…Illegal releases from aquaria, garden ponds or bait buckets, or planned stocking within fisheries‐management activities represent anthropogenic pathways that assist in colonisation of human‐made freshwater systems with fishes. Indeed, human‐assisted introductions today constitute the most common pathway of non‐native fish dispersal globally (Gozlan et al, ; Hirsch et al, ; Olden et al, ; Patoka et al, ). Thus, it is likely that most gravel pits are more rapidly colonised with fishes through anthropogenic than through natural means.…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanisms by which transoceanic dispersal of freshwater fishes could happen are difficult to evaluate because this kind of dispersal is rare and relatively improbable (although it becomes almost inevitable over geological timescales). Proposed mechanisms (not mutually exclusive) include formation of giant freshwater plumes following catastrophic events like typhoons or tropical river floods; rafting of large chunks of soil and vegetation [see Houle, for dispersal of terrestrial vertebrates, but these ‘floating islands’ might include puddles of fresh water as well]; ‘stepping‐stone’ dispersal across island arches (Gilpin, ; however, this mechanism may be unfeasable for freshwater organisms); or bird‐mediated zoochory of fish eggs (Hirsch et al ., 2018). Strikingly, most freshwater fish taxa for which transoceanic dispersal has been inferred possess peculiar physiological or behavioural adaptations (e.g.…”
Section: Historical Biogeography Of Widespread Freshwater Fish Cladesmentioning
confidence: 99%
“…(2) Oceanic dispersal in freshwater fishes Houle, 1998 for dispersal of terrestrial vertebrates, but these 'floating islands' might include puddles of fresh water as well]; 'stepping-stone' dispersal across island arches (Gilpin, 1980; however, this mechanism may be unfeasable for freshwater organisms); or bird-mediated zoochory of fish eggs (Hirsch et al, 2018). Strikingly, most freshwater fish taxa for which transoceanic dispersal has been inferred possess peculiar physiological or behavioural adaptations (e.g.…”
Section: Historical Biogeography Of Widespread Freshwater Fish Clamentioning
confidence: 99%
“…However, a recent thorough review failed to provide solid empirical evidence for such dispersal (Hirsch et al. ). We discovered an alternative mode to waterbird‐facilitated dispersal of fish eggs—inside the alimentary system of coscoroba swan (form of endozoochory)—and experimentally demonstrated that killifish eggs from bird feces were capable of continuing their development after spending over 30 h inside a swan (Fig.…”
mentioning
confidence: 99%